International human rights law - Smith, Rhona K. M. (Oxford: Oxford University Press, 2022)
Illustrating the scope of this fascinating and wide-reaching subject to the student, this clear and concise text gives a broad introduction to international human rights law. Coverage includes regional systems of protection, the role of the UN and a variety of substantive rights. The author skilfully guides students through the complexities of the subject, and then prepares them for further study and research.
Includes bibliographical references and index.
Buku bacaan asas siswazah Fakulti Pengajian Islam.
Keywords: Human rights; International law and human rights